Integrated Analysis of lncRNA and mRNA Transcriptomes Reveals New Regulators of Ubiquitination and the Immune Response in Silica-Induced Pulmonary Fibrosis. (13th January 2019) - Zhou, Yao; He, Li; Liu, Xiao-Dan; Guan, Hua; Li, Ying; Huang, Rui-Xue; Zhou, Ping-Kun
Abstract : Objectives . As an epigenetic player, long noncoding RNAs (LncRNAs) have been reported to participate in multiple biological processes; however, their biological functions in silica-induced pulmonary fibrosis (SIPF) occurrence and development remain incompletely understood. Methods . Five case/control pairs were used to perform integrated transcriptomes analysis of lncRNA and mRNA. Prediction of lncRNA and mRNA functions was aided by the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Additionally, we constructed a coexpression network of lncRNAs and mRNAs to identify targets of regulation. Results . In total, 1069 differentially expressed mRNAs and 366 lncRNAs were identified with the changes more than 2 times (p<0.05), of which 351 downregulated mRNA and 31 downregulated lncRNA were <0.5 (p<0.05) and those of 718 upregulated mRNAs and 335 upregulated lncRNA were >2 (p<0.05). The levels of 10 lncRNAs were measured via qRT-PCR; the results were consistent with the microarray data. Four genes named of FEM1B, TRIM39, TRIM32, and KLHL15 were enriched significantly with ubiquitination and immune response. Cytokine-cytokine receptor interaction was the most significantly enriched KEGG pathway in both mRNAs and lncRNAs. The coexpression network revealed that a single lncRNA can interact with multiple mRNAs, and vice versa. Conclusions . lncRNA and mRNA expression were aberrant in patients with SIPF compared to controls, indicating that differentially expressed lncRNAs and mRNAs may play critical roles in SIPF development. Our study affords new insights into the molecular mechanisms of SIPF and identifies potential biomarkers and targets for SIPF diagnosis and treatment.